Effect of beta-Carotene from Yellow Ambon Banana Peel on Rat Serum Retinol Level - Suparmi, Suparmi; Prasetya, Harka; Martosupono, Martanto; Sunaryanto, Lasmono Tri (Chemistry Department, The University of Brawijaya, 2014)
Vitamin A Deficiency (VAD) is associated with significant morbidity and mortality from common childhood infections and is the world’s leading preventable cause of childhood blindness. Studies showed that carotenoid is one of the promissed vitamin A source. However the studies on carotenoid from yellow banana peel and its potential as a natural source of vitamin A has not been widely reported. This study was conducted to measure the blood serum retinol levels of rats after administration of β-carotene from yellow ambon banana peel. This was an experimental study with post test only control group design, with sample size of 18 rats with age 1 month, devided into 3 groups. β-carotene dose administered based on the dose of red capsules vitamin A are (200,000 doses SI) for toddlers aged 12-59 months. Serum retinol levels were measured using a spectrophotometer according metide. This present study showed that the blood serum level in group treated with of β - carotene from yellow ambon banana peel (28.35 ± 1.61 mg/ dL ), was significantly different (p < 0.05) from that of control group ( 22.08 ± 1.35 mg /dL ). β-carotene from yellow ambon banana peel are potential as provitamin A.